OUTPUT OF FINISHED PRODUCT IN FLOUR PRODUCTION (Multidisciplinary Journal of Science and Technology, 2024)
This article investigates the processes involved in the production of flour and the factors influencing the output of finished products. By analyzing existing literature and conducting empirical studies, the research aims to provide a comprehensive overview of optimizing flour production. The study identifies key variables affecting production efficiency and suggests methodologies for improving yield and quality.